Návrh marketingové strategie firmy YONEX - zavedení nového výrobku na český trh - Navrátilová, Anna (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce je věnována problematice zavedení nového typu sportovních bot značky Yonex na český trh. Práce je rozdělena do více částí. První je především zaměřena na teoretický rozbor standardního postupu zavedení nového produktu na trh, který bývá uváděn v odborných publikacích. Druhá, praktická část analyzuje postup zavedení nového typu bot ve florbalové divizi Yonex na český trh. Třetí, závěrečná část práce je zhodnocení marketingové strategie firmy Yonex a stanovení doporučení, jak připravenou strategii zavedení produktu realizovat. Požadovaným výstupem práce je vyhodnocení analýzy a stanovení již zmíněných doporučení, které mohou proces zavádění nových produktů firmy Yonex zlepšit a popřípadě i celý proces usnadnit.

Master's Thesis deals with the launch of a new type of indoor sports shoes Yonex to the Czech market. The thesis is divided into several parts. The first is focused on theoretical analysis of the standard procedure for introducing of new products to the market which we are able to find in professional publications. The second, practical part analyses the introduction procedure of new indoor shoes in new floorball division of Yonex Company to the Czech market. The third, final part of this thesis includes evaluation of Yonex Floorball marketing strategy and recommendations for implementation and improvement for the launch procedure. The required outcome of this work is evaluation of the analysis and set a few mentioned recommendations, which can improve the launch process of the new floorball division of Yonex and simplify the process for the future.
Marketing Strategy Design for Yonex Company - new Product Launch in the Czech Republic
Keywords: Vstup na nový trh; marketingová strategie; analýza trhu; marketingový mix; Entrance to a new market; markting strategy market analysis; marketing mix